ANALISIS PERAWATAN OVERHAUL TERHADAP PENINGKATAN KUALITAS ISOLASI STATOR PADA MOTOR INDUKSI 410 KW 6000 V - Prima Firdaus (2023)
With the growth of the manufacturing industry in Indonesia, it will have an impact on the increasing use of induction motors as one of the supporting tools for production. One part in an induction motor that is often damaged is the insulator as a protector that separates the stator conductors. With the high frequency of use, sooner or later the insulator on the stator will experience degradation or even complete damage. Therefore, scheduled maintenance is needed to monitor the condition of the quality of insulation. This study will discuss the effect of overhaul maintenance on improving insulation quality on induction motors of the tohsiba brand 410 kw 6000 V. By comparing test results before and after maintenance and assessing the feasibility of using the motor. The main parameters of the analysis are insulation resistance, leakage current and winding resistance.